2021
DOI: 10.1007/s11192-021-04118-3
|View full text |Cite
|
Sign up to set email alerts
|

A credit-like rating system to determine the legitimacy of scientific journals and publishers

Abstract: The predatory nature of a journal is in constant debate because it depends on multiple factors, which keep evolving. The classification of a journal as being predatory, or not, is no longer exclusively associated with its open access status, by inclusion or exclusion on perceived reputable academic indexes and/or on whitelists or blacklists. Inclusion in the latter may itself be determined by a host of criteria, may be riddled with type I errors (e.g., erroneous inclusion of a truly predatory journal in a whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 94 publications
(84 reference statements)
0
6
0
1
Order By: Relevance
“…Teixeira da Silva et al [53] suggested a layer of classification, such as a credit-like rating, that can be used alone, or as an overlay to a more quantitative system of ranking behavior, such as the "Predatory Score" [54]. In such a system, concrete criteria are ranked, and a qualitative system of terminology, or color coding, is overlaid, to provide a score that reflects the attribution of positive points for scholarly behavior, but discounts points for unscholarly behavior.…”
Section: How Do Academics Protect Themselves Against Predatory Publis...mentioning
confidence: 99%
“…Teixeira da Silva et al [53] suggested a layer of classification, such as a credit-like rating, that can be used alone, or as an overlay to a more quantitative system of ranking behavior, such as the "Predatory Score" [54]. In such a system, concrete criteria are ranked, and a qualitative system of terminology, or color coding, is overlaid, to provide a score that reflects the attribution of positive points for scholarly behavior, but discounts points for unscholarly behavior.…”
Section: How Do Academics Protect Themselves Against Predatory Publis...mentioning
confidence: 99%
“…Second, while I am largely "silent" (in Dunleavy, 2021) about contextual factors in scholarly publishing (e.g., increasing numbers of submissions, a "publish or perish" culture, lack of qualified reviewers, the rise of predatory publishing, etc.) -I am by no means ignorant of them (see Dunleavy, 2019;2020a, 2020bDunleavy & Hendricks, 2020;Teixeira da Silva et al, 2021). Rather, the point I was trying to convey in my original essay was that the deficiencies of traditional peer review are present regardless of these broader trends and shifts.…”
Section: In Silence/words Awaymentioning
confidence: 99%
“…In a similar vein, scholars have attempted to differentiate between quality, trustworthy, or "reputable" journals on the one hand, and untrustworthy or so-called "predatory" ones, through the creation of various whitelists and blacklists (Beall, 2010(Beall, , 2014Bisaccio, 2018;Grudniewicz et al, 2019;Laine & Winker, 2017;Teixeira da Silva et al, 2021). The underlying aim here is largely the same -journals found on blacklists are often viewed as containing weak, fraudulent, or otherwise flawed scholarship (i.e., they are "bad journals" and to be avoided).…”
Section: Introductionmentioning
confidence: 99%